Um caminho para a liberdade: a Lei Rio Branco na crise do sistema escravista paraibano - Lyra Filho, Giuseppe Emmanuel (2020)
The main research theme of this study is the analysis of the application and the impacts of the Rio Branco Law of 1871 on the crisis of the Brazilian slave system, specifically in the province of Paraíba in the 1870s and 1880s, considering the cases of children who were born free after the enactment of the Law, known as ingênuos, the diverse and enslaved subjects and families who were granted or conquered manumission mediated by the State, by means of the Emancipation Fund. Throughout the 19th century, several proposals were made for the abolition of slavery, mostly based on an emancipationist perspective, which predicted a gradual and slow abolition of slavery, without affecting agricultural properties, but they were not put into practice. Only in 1871, with the approval of the Rio Branco Law, this emancipationist project was enacted specifically with the purpose of solving the problem of slavery in an ordered and peaceful approach. Together with a slavery crisis in Brazil, the Rio Branco Law was applied in the province of Paraíba, with some results and various limits. Therefore, we analyze the impacts of this legislation on the province of Paraíba. Furthermore, we present some social subjects that were granted liberty by means of the Law of 1871. Our theoretical basis was the discussions related to the Social History of Slavery in dialogue with the Political History, focused on the relation between the Laws and the historical processes, with a great influence of E. P. Thompson and the recent historiography of the Brazilian slavery that guided the studies of the laws as a means of disputes and social conflicts within the slave society. We used a quite varied documentary corpus: Annals of the Chamber of Deputies and of the Federal Senate, Reports of the presidents of province, newspapers, baptism records, reports of the Ministry of Agriculture, and letters of the Classification Boards of Paraíba, which led us to identify the ingênuos from Paraíba, the data on the application of the Emancipation Fund and the enslaved subjects and families that were granted the liberty by this means, as well as to understand the Law of 1871 as a constituent of the slavery crisis of Paraíba. Thus, this work was conducted together with the Postgraduate Program in History, with the concentration area in History and Historical Culture, and in the line of research in History and Regionalities.